Effectiveness of using integrated algorithm in preserving privacy of social network sites users - Kavianpour, S. (Springer-Verlag Berlin Heidelberg, 2011)
Social Network Sites (SNSs) are one of the most significant and considerable topics that draw researches attention nowadays. Recently, lots of people from different areas, ages and genders join to SNSs and share lots of different information about various things. Spreading information can be harmful for users' privacy. In this paper, first we describe some definitions of social networks and their privacy threats. Second, after reviewing some related works on privacy we explain how we can minimize the information disclosure to adversaries by using integrated algorithm. Finally we try to show the effectiveness of proposed algorithm in order to protect the users' privacy. The enhanced security by anonymizing and diversifying disclosed information presents and insures the paper aim.